2023
DOI: 10.3389/fendo.2023.1223583
|View full text |Cite
|
Sign up to set email alerts
|

The role of m6A and m6Am RNA modifications in the pathogenesis of diabetes mellitus

Abstract: The rapidly developing research field of epitranscriptomics has recently emerged into the spotlight of researchers due to its vast regulatory effects on gene expression and thereby cellular physiology and pathophysiology. N6-methyladenosine (m6A) and N6,2’-O-dimethyladenosine (m6Am) are among the most prevalent and well-characterized modified nucleosides in eukaryotic RNA. Both of these modifications are dynamically regulated by a complex set of epitranscriptomic regulators called writers, readers, and erasers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Our data revealed that the m6A modification of the NDUFB5 3’UTR was significantly reduced in HUVECs treated with AGEs, which drove us to further explore the methyltransferase that mediates NDUFB5 m6A modification. METTL3 is the first m6A methyltransferase to be discovered and is the catalytic core component of the m6A methyltransferase complex [ 54 ]. Previous studies have reported that high glucose and AGEs induce METTL3 expression to promotes the progression of diabetic bone loss [ 22 ], diabetic retinopathy [ 23 ], and diabetic nephropathy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that the m6A modification of the NDUFB5 3’UTR was significantly reduced in HUVECs treated with AGEs, which drove us to further explore the methyltransferase that mediates NDUFB5 m6A modification. METTL3 is the first m6A methyltransferase to be discovered and is the catalytic core component of the m6A methyltransferase complex [ 54 ]. Previous studies have reported that high glucose and AGEs induce METTL3 expression to promotes the progression of diabetic bone loss [ 22 ], diabetic retinopathy [ 23 ], and diabetic nephropathy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The m 6 A modification is defined as methylation of the N6 position of adenosine and occurs in the common sequence DRACH (D = G/A/U, R = G/A, and H = A/C/U) ( 11 , 12 ), which usually locates in the 3′-untranslated regions (UTRs), coding sequences, around stop codon regions, and 5′-UTRs ( 13 , 14 ). This process orchestrates intricate regulatory networks on RNA, covering the reversible and dynamic interplay among methylases (writers), demethylases (erasers) and m6A-binding proteins (readers) ( 15 ).…”
Section: The Regulation Of Rna M 6 a Modificationmentioning
confidence: 99%